Photobiomodulation as a preventive strategy for oral mucositis in pediatric oncology: a systematic review and meta-analysis - Marques, Mariana Takatu [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
Objectives: Oral mucositis (OM) is one of the most frequent and debilitating complications in children undergoing treatment for hematologic malignancies. Current management strategies focus on minimizing OM severity and alleviating symptoms. This systematic review aimed to evaluate the effectiveness of photobiomodulation (PBM) in preventing OM in pediatric patients with hematologic malignancies receiving chemotherapy. Data/Sources: Guided by the PICOS framework, this review addressed the following research question: Is PBM therapy effective in reducing the incidence and severity of oral mucositis in children and adolescents with hematologic malignancies undergoing chemotherapy? A comprehensive search was conducted in PubMed, Scopus, Web of Science, Embase and The Cochrane databases through February 2025. Eligible studies were randomized clinical trials involving patients aged 0–22 years diagnosed with hematologic malignancies treated by means of chemotherapy, and undergoing preventive PBM therapy for OM. Study Selection: Five randomized controlled trials were included, encompassing patients aged 4 months to 22 years. Of these, 97 received low-level laser therapy (LLLT) and 80 received light-emitting diode therapy (LEDT). PBM was consistently reported as effective in preventing the onset and reducing the severity of OM in these populations. Three studies were eligible for meta-analysis, which demonstrated a statistically significant benefit of PBM therapy (p = 0.04), with a 95% confidence interval ranging from 0.01 to 0.84. Conclusions: PBM therapy appears to be an effective preventive strategy for oral mucositis in pediatric patients undergoing chemotherapy for hematologic malignancies. Further large-scale trials are warranted to establish standardized protocols and optimize treatment outcomes. Clinical Significance: PBM therapy significantly reduces the incidence and severity of oral mucositis in pediatric patients undergoing chemotherapy for hematologic malignancies. This non-invasive intervention offers an emerging preventive strategy, improving patient comfort and treatment adherence. Standardized PBM protocols may enhance supportive care in pediatric oncology settings.

Objetivos: A mucosite oral (MO) é uma das complicações mais frequentes e debilitantes em crianças em tratamento de neoplasias hematológicas. As estratégias atuais de manejo concentram-se em minimizar a gravidade da MO e aliviar os sintomas. Esta revisão sistemática teve como objetivo avaliar a eficácia da fotobiomodulação (FBM) na prevenção da MO em pacientes pediátricos com neoplasias hematológicas submetidos à quimioterapia. Dados/Fontes: Orientada pelo modelo PICOS, esta revisão abordou a seguinte pergunta de pesquisa: A terapia de FBM é eficaz na redução da incidência e da gravidade da mucosite oral em crianças e adolescentes com neoplasias hematológicas sob tratamento quimioterápico? Foi realizada uma busca abrangente nas bases PubMed, Scopus, Web of Science, Embase e Cochrane até fevereiro de 2025. Foram considerados elegíveis estudos clínicos randomizados envolvendo pacientes de 0 a 22 anos diagnosticados comneoplasias hematológicas, tratados com quimioterapia e submetidos à FBM preventiva para MO. Seleção dos Estudos: Cinco ensaios clínicos randomizados foram incluídos, englobando pacientes de 4 meses a 22 anos. Destes, 97 receberam terapia com laser de baixa potência (LLLT) e 80 receberam terapia com diodo emissor de luz (LEDT). A FBM foi consistentemente relatada como eficaz na prevenção do surgimento e na redução da gravidade da MO nessa população. Três estudos foram elegíveis para a meta-análise, que demonstrou um benefício estatisticamente significativo da terapia com FBM (p = 0.04), com intervalo de confiança de 95% variando de 0.01 a 0.84. Conclusões: A terapia com FBM mostrou ser uma estratégia preventiva eficaz para mucosite oral em pacientes pediátricos submetidos à quimioterapia para neoplasias hematológicas. Ensaios adicionais, de maior escala, são necessários para estabelecer protocolos padronizados e otimizar os resultados do tratamento. Relevância Clínica: A terapia com FBM reduz significativamente a incidência e a gravidade da mucosite oral em pacientes pediátricos submetidos à quimioterapia para neoplasias hematológicas. Essa intervenção não invasiva representa uma estratégia preventiva promissora, melhorando o conforto do paciente e a adesão ao tratamento. Protocolos padronizados de FBM podem aprimorar o cuidado de suporte em cenários de oncologia pediátrica.
Fotobiomodulação como estratégia preventiva para mucosite oral em oncologia pediátrica: uma revisão sistemática e meta-análise
Keywords: Terapia com luz de baixa intensidade; Crianças; Câncer; Stomatitis; Stomatitis